Development of a wearable surface enhanced Raman scattering sensor chip based on silver nanowires for rapid detection of urea, lactate and pH in sweat - D’Andrea Cristiano; Banchelli Martina; Amicucci Chiara; Polykretis Panagis; Micheletti Filippo; de Angelis Marella; Hwang Byungil; Matteini Paolo (Journal of the European Optical Society-Rapid Publications, 2024)
A wearable sweat sensor chip based on surface-enhanced Raman spectroscopy (SERS) is here presented. The plasmonic core of the chip, obtained by deposition of silver nanowires on a polytetrafluoroethylene (PTFE) porous membrane, permits the direct and label-free detection of urea and lactate at physiologic concentrations in combination with the pH measurement in the range between 5 and 9. Once integrated with commercial biocompatible and adhesive tape layers, the as produced SERS-active chip provides a low-cost, flexible and wearable sensing device for rapid and reliable human sweat analysis. The chip was finally tested on real sweat samples to estimate lactate and urea during medium-intense exertions.